Level of Erosion Hazard in Buffer Zone of Great Forest Park Sultan Syarif Hasyim Riau. Issue 1 (April 2020) - Hadinoto, Hadinoto; Suhesti, Eni; Ikhwan, Muhammad
Abstract: The buffer zone of Great Forest Park Sutan Syarif Hasyim, is adjacent to the conservation area that must be protected. Conditions of this hilly area there are water dams and some areas open because of forest burning. In the area there are traces of human activities to open and work the land. This will result in erosion, which impacts the silting of the dam. The purpose of this study is to identify the level of erosion hazard. This research uses survey method. Data retrieval is done by field checks. The data taken, among others; land cover or land use pattern and soil type at the study site. The result of calculation of erosion rate value by using USLE formula then classified into five classes, which is very light, light, medium, heavy, and very heavy. The level of erosion hazard for the area around the dam at the study site shows the category from mild to moderate. The lowest alleged soil erosion is found in the forest and highest in agricultural crops. The area of agricultural crops has a category of erosion hazard at a moderate level with an estimated erosion of 68.19 tonnes / ha / year. And areas with forest cover in the category of light erosion hazard with an estimated erosion of 27.15 tonnes / ha / year